Migration of Health Workers The UK Perspective to 2006 - Buchan, James (OECD Health Working Papers, 2008)
The UK has a population of 56 million, and most healthcare is delivered through the National Health Service (NHS). The NHS employs more than one million staff. In the late 1990s shortages of skilled staff were a main obstacle to improving services in the NHS. The response by government was to "grow" the NHS workforce. There are four main policy options to "grow" the workforce- increase home based training; improve retention rates of current staff (to reduce need to recruit additional staff); improve "return" of staff currently not practising; and internationally recruit health professionals. International recruitment was used to achieve rapid growth in the NHS workforce. It was facilitated by fast tracking work permits for health professionals, by targeting recruits in specified countries, using specialist recruitment agencies, and by co-ordinating local level recruitment within the NHS (...)